Prácticas de enseñanza de Lógica-Matemática de Inicial II en el Centro de Desarrollo Infantil Manitas Libres - Cabanilla Guillén, Mishel Vanessa (2016)
The work is implemented for academic purposes. It is Performs in an institution in the sector of the "Pinar alto". The "Manitas libres". Child development center has initial II level which is considered to perform the observation on children of four to five years of age in the area of mathematical logic. The Research has a methodological Foundation as a qualitative method; The latter is supported by these being data collection tools: semi-structured interview, Journal of field and observation sheets. The theoretical foundations which are considered as main axes in the present investigation, seeks to explain the variables at cognitive development in the area of mathematical logic: planning, medotolical estructure, student-teacher relation, evaluation proceses and homework’s. It seeks to understand these areas in order to reach an understanding of the main variables that influence the process of learning, it is also necessary to give importance to the process that is the teacher at the time of implementing the necessary tools to facilitate the teaching-learning process. At the end of the investigation we find an analysis of results, which seeks to combine the tools implemented to make the observation with the theory on which is based the work. The main conclusion is: how the teaching process and learning is achieved when the two sides both student and teachers possess the necessary tools to optimize the capabilities of each, this is achieved when a correct micro performed.